A Single Step CPM Time-Cost Tradeoff Algorithm - Kaur, Gurpreet (My University, 2010)
The development and use of the time-cost tradeoff for a project network is an essential part of a CPM (Critical Path Method) analysis, since small variations in project duration could heavily affect the project's cash flow. Managing projects involves the usual management functions of planning, scheduling and controlling. CPM, which is a planning tool, helps to do all three. One of the most salient features of CPM is the attempt to optimize the total project cost (when project duration must be reduced) by shortening appropriate project activities. CPM is a bottleneck route that reduces over all project time and provides a cost evaluation of "Crash" programs. CPM focused on optimizing the total costs (i.e., overhead plus activity costs) for various possible project completion dates; however, no systematic procedure was initially proposed to effectively achieve this goal of cost optimization. Present thesis deals with a single step CPM time-cost tradeoff algorithm for efficiently shortening the duration of a project when the expected project duration is incompatible (exceeds) with pre-determined or externally imposed requirements. Thesis contains three chapters; first chapter is introductory in nature and also contains a brief review of literature related to the topic. In second chapter, two distinct algorithms on CPM time-cost tradeoff have been reviewed. In third chapter, a single step CPM time-cost algorithm has been given consisting of a combination of previously discussed two algorithms in second chapter
MSc
Keywords: CPM time-cost tradeoff; Project Management